Antecedent Disease and Amyotrophic Lateral Sclerosis: What Is Protecting Whom? - Hollinger, Sabrina K.; Okosun, Ike S.; Mitchell, Cassie S. (Frontiers in Neurology, 2016)
Multiple studies have shown that antecedent diseases are less prevalent in Amyotrophic Lateral Sclerosis (ALS) patients than the general age-matched population, which suggests possible neuroprotection. Antecedent disease could be protective against ALS or, conversely, the asymptomatic early physiological underpinnings of ALS could be protective against other antecedent disease. Elucidating the impact of antecedent disease on ALS is critical for assessing diagnostic risk factors, prognostic outcomes, and intervention timing. The objective of this study was to examine the relationship between antecedent conditions and ALS onset age and disease duration. Medical history surveys for 1,439 Emory ALS Clinic patients (Atlanta, GA, USA) were assessed for antecedent hypertension, hyperlipidemia, diabetes, obesity, asthma, arthritis, chronic obstructive pulmonary disease (COPD), thyroid, kidney, liver, and other non-ALS neurological disease. The ALS onset age and disease duration is compared between the antecedent and non-antecedent populations using Chi square, Kaplan Meier, and ordinal logistic regression. When controlled for confounders, antecedent hypertension (high blood pressure), hyperlipidemia (high cholesterol), arthritis, COPD, thyroid disease and non-ALS neurological disease are found to be statistically associated with a delayed onset age whereas antecedent obesity (body mass index, BMI > 30) was correlated with earlier ALS onset age. With the potential exceptions of liver disease and diabetes (the latter without other common co-morbid conditions), antecedent disease is associated with overall shorter disease duration. The unique potential relationship between antecedent liver disease and longer ALS disease duration warrants further investigation, especially given liver disease was found to be a factor of 4-7 times less prevalent in ALS. Notably, most conditions associated with delayed ALS onset are also associated with shorter disease duration. Pathological homeostatic instability exacerbated by hypervigilant regulation (over-zealous homeostatic regulation due to too-high regulatory feedback gains) is a viable hypothesis for explaining the early-life protection against antecedent disease and the overall lower antecedent disease prevalence in ALS patients; the later ALS onset age in patients with antecedent disease; and the inverse relationship between ALS onset age and disease duration.